Penanaman Nilai-Nilai Karakter Terintegrasi Self – Confidence pada Mata Pelajaran Bahasa Inggris Siswa Sekolah Dasar - Alawiyyah, Anisa; Apsoh, Siti (Universitas Muhammadiyah Magelang, 2019)
The purpose of this study was to determine the implementation of the inculcation of the values ​​of the integrated character of self-confidence inside and outside the classroom and their impact on grade IV SDIT Mutiara students. The research method used is descriptive qualitative. The stages of this research method are collecting data by observation, interview, questionnaire, document analysis and data processing. The instruments used in this study were assessment rubrics, teacher interview guidelines, teachers and student questionnaires. The results of research on the inculcation of the integrated character values ​​of self confidence in English subjects in the classroom have been successfully applied. While outside the classroom the most prominent religious character values. The barriers there are not available in English books and character values ​​assessment format, the family environment of students who are less concerned about the character values ​​that have been applied in the School and students get different average grades but tend to be quite good.